Studying Hueckel Edge Detector Using Binary Step Edge Image - Abdul-jabbar, Hameed Majeed; Naji, Taghreed Abdul-Hameed; Hatem, Amal Jabbar; Abdul-Ameer, Inbethaq Mohammed Ali (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Hueckel edge detector study using binary step edge image is presented. The standard algorithm that Hueckel presented, in his paper without any alteration is adopted. This paper studies a fully analysis for the algorithm efficiency, time consuming and the expected results with slide window size and edge direction. An analysis for its behavior with the changing of the slide window size (disk size) is presented. The best result is acquired when the window size equals to four pixel.